2004
DOI: 10.1007/978-3-540-28632-5_9
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Elliptic Curve Cryptography and RSA on 8-bit CPUs

Abstract: Abstract. Strong public-key cryptography is often considered to be too computationally expensive for small devices if not accelerated by cryptographic hardware. We revisited this statement and implemented elliptic curve point multiplication for 160-bit, 192-bit, and 224-bit NIST/SECG curves over GF(p) and RSA-1024 and RSA-2048 on two 8-bit microcontrollers. To accelerate multiple-precision multiplication, we propose a new algorithm to reduce the number of memory accesses. Implementation and analysis led to thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
656
0
13

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 871 publications
(671 citation statements)
references
References 7 publications
2
656
0
13
Order By: Relevance
“…Also our code size is considerable smaller, which directly translates into savings in silicon area when the program code is stored in on-chip ROM. [12] 8051 (CC1010) ECC 160 bit GF(p) 14.74 4,580.0 67.53M Gura [12] 8051 (CC1010) ECC 192 bit GF(p) 14.74 7,560.0 111.48M Gura [12] AVR (ATmega128) ECC 160 bit GF(p) 8.00 810.0 6.48M Gura [12] AVR ( …”
Section: Implementation Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Also our code size is considerable smaller, which directly translates into savings in silicon area when the program code is stored in on-chip ROM. [12] 8051 (CC1010) ECC 160 bit GF(p) 14.74 4,580.0 67.53M Gura [12] 8051 (CC1010) ECC 192 bit GF(p) 14.74 7,560.0 111.48M Gura [12] AVR (ATmega128) ECC 160 bit GF(p) 8.00 810.0 6.48M Gura [12] AVR ( …”
Section: Implementation Resultsmentioning
confidence: 99%
“…Recent research has shown that highly-optimized software implementations can reach sub-second performance on the ATmega128 [12], but not on a standard 8051 microcontroller, at least not if the order of the finite field is 160 bits or more [12,16,24]. The main reason is the rather poor performance of a standard 8051 in relation to the ATmega128 (see Appendix A).…”
Section: Hardware/software Boundaries and Trade-offsmentioning
confidence: 99%
See 1 more Smart Citation
“…Performing public key encryption on 8-bit microcontrollers has been enhanced by the use of Elliptic Curve Cryptography (ECC) (Koblitz, 1987;Miller, 1986). ECC reduces the time and power requirements for the same level of encryption as an equivalent Rivest, Shamir, and Adleman public key cryptography (RSA) public-key encryption (Rivest, Shamir & Adleman, 1978) by an order of magnitude (Gura et al, 2004;Sethi, Arkko & Keranen, 2012): RSA encryption on constrained 8-bit microcontrollers may take minutes to complete, whereas similar ECC-based cryptography completes in seconds. However, despite the fact that ECC enables 8-bit microcontrollers to participate in public-key encryption systems, in many cases it is not used.…”
Section: B1: Network Confidentialitymentioning
confidence: 99%
“…At CHES 2004, Gura et al presented a landmark paper in which they compared ECC with RSA on 8-bit CPUs and introduced the now-classical hybrid method for multiplication [9]. The hybrid method exploits the large register file of the AVR platform to store several bytes of the operands in registers and, in this way, combines the advantages of the product scanning and operand scanning technique [10].…”
Section: Introductionmentioning
confidence: 99%